Penerapan Fungsi Manajemen dalam Peningkatan Kualitas Pelayanan Jamaah Pada Pengelolaan Masjid Kampus: Studi Kasus Masjid Fathullah Uin Syarif Hidayatullah Jakarta - Anis Mas’udah; Mazidah M; Irfan Muhammad D; Mita Aulia Putri; Rizky Saputra; Zahra Zahwa M; Sugiharto S (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Campus mosque plays a strategic role not only as a place of worship but also as a center for faith development, da’wah education, and social activity for the academic community. Beyond these functions, the quality of service provided to the congregation (jamaah) has become an increasingly important indicator of how well a campus mosque is managed. This study aims to analyze the implementation of management functions (planning, organizing, actuating, and controlling) and riayah (facility maintenance) in the management of Fathullah Mosque at Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, and to examine how the application of these functions contributes to improving the quality of service experienced by the congregation. The study employed a qualitative descriptive method with a case study approach, using field observation, an in-depth interview with the Chairperson of the Fathullah Mosque Prosperity Board (Dewan Kemakmuran Masjid), and documentation study. Service quality was assessed using five dimensions adapted from the SERVQUAL framework, namely tangibility, reliability, responsiveness, assurance, and empathy. The findings indicate that Fathullah Mosque has implemented management functions reasonably well, as reflected in its clear vision and mission, an organized administrative structure divided into five working fields, regular daily, weekly, and annual programs, and adequate facilities. A SWOT analysis reveals that the mosque’s main strength lies in strong institutional support from the university and the availability of academically qualified human resources, while its main weakness is the limited use of digital technology in management, publication, and service evaluation.